The cycle network: a latent environmental infrastructure: Managing urban flooding in the region of Abruzzo - Clemente, Antonio Alberto (TeMA - Journal of Land Use, Mobility and Environment, 2022)
The topic to be investigated is the potential interdependence between the cycling network and the management of rainwater in the mid-Adriatic region of Abruzzo. Preliminarily, two observations. The first concerns cycling: in Italy it is constantly increasing, both in terms of territorial diffusion and turnover. The second: the frequency of urban flooding, resulting from extreme atmospheric phenomena, has been constantly increasing. However, cycling and urban flooding are two issues addressed separately. The first is framed as a contribution to slow mobility. The second is treated as a continuing emergency. The goal is to overcome separateness. And imagine the cycle network as an environmental infrastructure that, in addition to supporting the transit of bicycles, can contribute to a better collection and management of rainwater too, as an alternative to the sewer system. This hypothesis works on those cities that have transformed water from an agent that generates dangerous conditions, into a strategic resource. Methodologically, the projects and intervention programs will be compared to the: network space, space associated with the network and context space. The comparison aims to provide some lines of action useful for orienting the actions of the urban plan in the mid-Adriatic region of Abruzzo of Abruzzo.